Nationalism and the birth of modern art in Egypt - Miller, E (2012)
This dissertation covers the emergence of a tradition of the fine arts in Egypt during the first half of the twentieth century and its relationship to discourses of nationalism. Taking as a starting point the canon of the ‘pioneer’ generation as it is defined in the historiography, I follow the careers of the sculptor Mahmud Mukhtar and the painters Ragheb ‘Ayyad, Muhammad Nagi, and Mahmud Sa‘id, each of whom is treated in a full chapter. Narratives surrounding the life and work of these artists have tended to emphasize the ways in which the images they created participated in the definition of a single cohesive nation – through the use of Pharaonic imagery, which anchors the nation in a distant past, through rural symbolism, which ties the nation to the land and the Nile, and through a female iconography that links the nation to ideas of virtue and purity – what I term here, following Timothy Mitchell and Homi Bhabha, a pedagogical narrative of the nation. However, I suggest that the process of imagining the nation as a unified whole necessarily involves a negotiation of difference, sometimes that of the peasant or the woman who pose a challenge to the assumption of an unproblematic national collectivity, sometimes that of the artists themselves, who, for reasons of foreign education, religion, or social identity, are unable to fully identify with definitions of the nation that were themselves constantly contested. This negotiation of difference – what Mitchell has termed the performative - and how it appears within works of visual art, constitutes the main subject of this dissertation.